The Darwin affair : a novel - Mason, Timothy, 1950- (Algonquin Books of Chapel Hill, 2019)
An ingenious mystery/thriller set in the mid-1800s in London, blending fictional characters and events with real characters, and featuring a detective intent on stopping a ruthless killer who has threatened the life of Queen Victoria.